Perception and expectation of elective Japanese language learners in Malaysian Higher Education Institution: a case study - Abdullah, Muhammad Alif Redzuan; Hussin, Sanimah (Macrothink Institute, 2021)
Japanese language course registered as either compulsory elective or free elective foreign language course at University Putra Malaysia (UPM). The Japanese language is the most popular among 11 foreign language courses offered for foreign language students who wish to take global languages proficiency courses. However, their achievements in the course are inadequate as most of them are incompetent in communication skills upon completion of the course. Therefore, this article aims to identify the perception of Japanese language students in UPM to enhance their understanding of the issue. This quantitative research applies questionnaires and random purposive sampling techniques as instruments for collecting data. The sampling consists of 84 students who had enrolled in Basic Japanese level 1course. The findings show there are significant factors attribute to students’ preference for learning the Basic Japanese language. The result of the study also indicated the Kana writing and numbers are easier to acquire compared to vocabulary, sentences, grammar, and particles in the Basic Japanese 1 course. The study also revealed that mastering vocabulary plays a vital role in speaking, reading, and writing well in the Japanese language. Therefore, this study suggests that the instructor should include more engaging activities, teaching aids, and tools in the classroom to make the teaching and learning process more conducive and friendly for the students to excel in this course.